KARAKTERISTIK POLA SEBARAN DAN MORFOMETRIK Enhalus acoroides DI PULAU BADAK BADAK KOTA BONTANG KALIMANTAN TIMUR - Restu Putri Ananda; Lily Inderia Sari; Aditya Irawan (Universitas Mataram, 2024)
Seagrass contributes to the productivity of coastal waters and plays an ecological role as a macro and micro habitat for organisms. The aim of the research is to determine the distribution and morphometric characteristics of E. acoroides on Badak Badak Island, Bontang City. This research was carried out in August 2023 – January 2024. Stands of E. acoroideswere calculated based on sub-station distribution using a 50x50cm square frame and for morphometric samples 5 stands of E. acoroides were taken in each square frame. Data analysis included the Morisita Dispersion Index as well as the size and ratio of leaf length and width, rhizome diameter and length, root diameter and length.The results showed that the distribution pattern of E. acoroides included uniform criteria. The average leaf width is 2.63cm and the average leaf length is 38.52cm with a ratio of 1:15, the average rhizome diameter is 14.19 mm and the rhizome length is 8.0 cm with a ratio of 1:6, the average root diameter 4.59 mm and average root length 12.52 cm with a ratio of 1: 27, and the ratio of rhizome length to root length is 1:2.